PENINGKATAN KEMAMPUAN BAHASA ANAK USIA DINI MELALUI PENGUNAAN FLASH CARD DI RA MIFTAHUL ULUM SUBANG - Latifah Munawaroh Latifah; Yuwan (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
The purpose of this study was to determine the development of language, especially aspects of phonology, in early childhood through the use of flashcard media. Language is the main need in human life, because it is used daily to interact and communicate in society. Every individual needs language, both to convey ideas and to understand the speech of others. This study uses the method of data collection through observation, interviews, and documentation. The results showed that in RA Miftahul Ulum there were several children aged 4-5 years who experienced an increase in language development, especially phonology, after using flashcard media. Based on these findings, it is recommended to early childhood educators to apply flashcard media as an alternative in improving children's language development.